Integrating Financial Literacy, Sustainability, and Industry Collaboration in Curriculum Development (Enhancing Maritime Education) - Alamsyah, Jaya; Susi Herawati; Natanael Suranta; Rizal Rochmansya; Gigih Prastyan Toko (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2024)
This research investigates the effectiveness of maritime education in addressing the evolving needs of the maritime industry, with a particular focus on shipping management, maritime business, financial literacy, and sustainability. The study employs qualitative methods, including semi-structured interviews with maritime professionals, educators, and graduates, to assess the alignment of current curricula with industry requirements. Results indicate that while maritime education provides a solid technical foundation, it falls short in integrating modern financial practices and sustainability principles. Stakeholder collaboration between industry professionals, educators, and students was found to be valuable but underdeveloped, highlighting the need for more structured partnerships. With an overall score of 9/10 across all indicators, the research suggests that incorporating financial decision-making and sustainability into the curriculum is essential for preparing graduates for future industry challenges. The study emphasizes the importance of adapting maritime education to equip students with the skills necessary to thrive in an increasingly complex and environmentally-conscious global maritime sector.